2020
DOI: 10.3390/molecules25153473
|View full text |Cite
|
Sign up to set email alerts
|

The Content of Phenolic Acids and Flavonols in the Leaves of Nine Varieties of Sweet Potatoes (Ipomoea batatas L.) Depending on Their Development, Grown in Central Europe

Abstract: The aim of the study was the qualitative and quantitative analysis of the bioactive components present in the leaves of 9 sweet potato cultivars grown in the moderate climate in Poland, which were harvested at different growth stages according to the BBCH (Biologische Bundesanstalt, Bundessortenamt und Chemische Industrie) scale (14, 51, 89). It was found that sweet potato leaves contained 7 polyphenolic compounds, including 5 chlorogenic acids—neochlorogenic acid (5-CQA), chlorogenic acid (3-CQA), 4-cryptochl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 38 publications
(45 reference statements)
1
20
0
Order By: Relevance
“…Krochmal-Marczak et al found that more flavonols were accumulated in mature leaves of sweet potato throughout the leaf growth period. 20 The secondary metabolite contents were related to leaf development and the synthesis rate and the activity of secondary metabolites decreased gradually with the development of leaves and cell proliferation. 21 The contents of six catechins were previously shown to be significantly different across five development periods in Camellia sinensis leaves, with the content of total catechins in tender leaves significantly higher than that in mature leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Krochmal-Marczak et al found that more flavonols were accumulated in mature leaves of sweet potato throughout the leaf growth period. 20 The secondary metabolite contents were related to leaf development and the synthesis rate and the activity of secondary metabolites decreased gradually with the development of leaves and cell proliferation. 21 The contents of six catechins were previously shown to be significantly different across five development periods in Camellia sinensis leaves, with the content of total catechins in tender leaves significantly higher than that in mature leaves.…”
Section: Resultsmentioning
confidence: 99%
“…According to Jung et al (1), the compound most abundant in sweet potato leaves is 5neochlorogenic acid (5-CQA), and its amount depends on different cultivars. In contrast, Krochmal-Marczak (19) noted that the chlorogenic acid (3-CQA) was the dominant CQA derivative. Our study found 1,4-diCQA, 3,5-diCQA, and 3-CQA to be the dominant CQA derivatives in the leaves of all six sweet potato cultivars.…”
Section: Quantified Concentrations Of Phenolic Compoundsmentioning
confidence: 95%
“…(16). The observed differences in phenolic components are likely due to the genetic composition of the varieties examined, the climate conditions, and the maturity of the leaves harvested in this study (19). The Supplementary Figures 1A-N shows the UV spectrum MS, MS/MS spectrum, and the chemical structures of the tentatively identified compounds.…”
Section: Total Phenolsmentioning
confidence: 99%
“…Among them, caffeic acid and caffeoylquinic acid derivatives, such as 4,5-di-O-caffeoylquinic acid, 3,4,5-tri-O-caffeoylquinic acid, 3-mono-O-caffeoylquinic acid, 3,4-di-O-caffeoylquinic acid, and 3,5-di-O-caffeoylquinic acid, are indicated as the main phenolic constituents in SPL [ 9 , 26 , 27 ]. These constituents are associated with the specific genotypes and the stages of leaf development [ 9 , 23 , 26 , 28 ]. The level of polyphenols in SPL varies among their varieties ranging from 0.3−13.5 g gallic acid equivalent (GAE)/100 g DW, which is 7–9 times higher than that levels found in grape seeds [ 29 ].…”
Section: Bioactive Compounds In Sweet Potato Leavesmentioning
confidence: 99%